“Sweet: I did it”! Measuring the sense of agency in gustatory interfaces - Vi, Chi Thanh; Cornelio, Patricia; Obrist, Marianna; Yeomans, Martin (Frontiers in Computer Science, 2023)
Novel gustatory interfaces offer the potential to use the sense of taste as a feedback modality during the interaction. They are being explored in a wide range of implementations, from chemical to electrical and thermal stimulation of taste. However, the fundamental aspect of gustatory interaction that has yet to be explored is the Sense of Agency (SoA). It is the subjective experience of voluntary control over actions in the external world. This work investigates the SoA in gustatory systems using the intentional binding paradigm to quantify how different taste outcome modalities influence users' SoA. We first investigate such gustatory systems using the intentional binding paradigm to quantify how different tastes influence users' SoA (Experiment 1). The gustatory stimuli were sweet (sucrose 75.31 mg/ml), bitter (caffeine powder 0.97 mg/ml), and neutral (mineral water) as the outcomes of specific keyboard presses. We then investigated how SoA was altered depending on users' sweet liking phenotype, given that sweet is one of the taste outcomes (Experiment 2), and in contrast with audio as a traditional outcome. In Experiment 2, stronger taste concentrations (sweet-sucrose 342.30g/L, bitter-quinine 0.1g/L, and neutral) were used, with only participants being moderate sweet likers. We further contrasted tastes with audio as the traditional outcome. Our findings show that all three taste outcomes exhibit similar intentional binding compared to auditory in medium sweet likers. We also show that longer action-outcome duration improved the SoA. We finally discuss our findings and identify design opportunities considering SoA for gustatory interfaces and multisensory interaction.